Melanin and lipofuscin as hallmarks of skin aging - Skoczyńska, Anna; Budzisz, Elżbieta; Trznadel-Grodzka, Ewa; Rotsztejn, Helena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Discoloration are symptoms of skin aging. They are connected with presence of melanin and lipofuscin, whose excess and abnormal distribution in the skin cause dark spots to appear. Melanin is formed under the influence of tyrosinase during melanogenesis. Its content changes with age, which may be a result of menopause. Lipofuscin is another example of the age pigment. It is composed of proteins, lipids and carbohydrates. It is described as an age pigment because its content increases with age. The formation and accumulation of lipofuscin is inevitable and leads to cell and homeostasis dysfunction because it reduces the proteasome activity.